Expert Analysis of Labeling and Packaging Products Manufactured Using Modern Technology in Order to Establish the Printing Method of its Details - M. V. Toropova (Теория и практика судебной экспертизы, 2023)
With the extensive implementation of new technologies in printing and reprographic printing the manufacturing methods of mass printing products, including labels, tags, and packaging, which often become the objects of forensic document analysis, have changed dramatically. The article describes the modern methods of color printing and reprographic printing used in manufacturing of such products. The work also provides an overview of the most common modern methods and types of color industrial printing used in the production of labels, tags, and packaging. The author describes the diagnostic complexes of features of these methods displayed at the raster level in the resulting prints (images).